The Relationship Between Premature Rupture of Membranes (PROM) and Leukocyte Levels in Newborns - Grovindo Grovindo; Sutriswanto Sutriswanto; Ari Nuswantoro; Panyada Cholsakhon (Borneo Scientific Publishing, 2025)
Premature Rupture of Membranes (PROM) remains a global concern in obstetrics due to its potential to cause complications such as infections that increase maternal and neonatal morbidity and mortality. PROM occurs in approximately 10–15% of pregnancies worldwide and 8–10% in Indonesia, often before 37 weeks of gestation, contributing significantly to preterm births and neonatal deaths. Risk factors for PROM include maternal age, parity, infection, and other pregnancy-related conditions. Infection resulting from PROM can be identified through leukocyte count in newborns, with leukocytosis indicating the presence of infection. This study aimed to examine the relationship between PROM and leukocyte levels in newborns at RSUD Drs. Jacobus Luna, M.Si, Bengkayang Regency, using a descriptive-analytic design with a cross-sectional approach and total sampling of 88 respondents. Results showed that among 36 newborns with elevated leukocyte levels, 28 cases (77.8%) were born from PROM pregnancies, whereas only 8 cases (22.2%) were non-PROM. Among 52 cases with normal leukocyte levels, only 11 newborns (21.2%) had PROM, while 41 (78.8%) did not. These findings indicate that newborns from PROM pregnancies tend to have higher leukocyte counts. Statistical analysis using Chi-square showed a significant relationship between PROM and leukocyte levels, with a p-value of 0.000 (< 0.05). In conclusion, PROM is a notable risk factor for increased leukocyte counts in neonates, underscoring the importance of early detection and management of PROM to reduce the risk of neonatal infection and its associated complications.